2023
DOI: 10.1136/bmjopen-2023-072188
|View full text |Cite
|
Sign up to set email alerts
|

Long-term psychosocial consequences of false-positive screening mammography: a cohort study with follow-up of 12–14 years in Denmark

Abstract: ObjectiveTo compare the long-term psychosocial consequences of mammography screening among women with breast cancer, normal results and false-positive results.DesignA matched cohort study with follow-up of 12–14 years.SettingDenmark from 2004 to 2019.Participants1170 women who participated in the Danish mammography screening programme in 2004–2005.InterventionMammography screening for women aged 50–69 years.Outcome measuresWe assessed the psychosocial consequences with the Consequences Of Screening–Breast Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…There is ongoing need to evaluate the psychological harms associated with screening, as is happening in the latest research, 43 and given recent advancements in novel cancer testing, diagnostics and technology that may one day be routinely implemented. 44,45…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is ongoing need to evaluate the psychological harms associated with screening, as is happening in the latest research, 43 and given recent advancements in novel cancer testing, diagnostics and technology that may one day be routinely implemented. 44,45…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing need to evaluate the psychological harms associated with screening, as is happening in the latest research, 43 and given recent advancements in novel cancer testing, diagnostics and technology that may one day be routinely implemented 44,45 . This goes beyond outcomes associated with false positive screening test results and includes true positive, false negative and abnormal test results, as well as other changes in cancer screening and early detection practices.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies demonstrating negative psychosocial impacts in other cancer screening programs with FP results. In breast cancer screening, more negative psychosocial consequences were noted in women who received FP results, with one study reporting persistent psychosocial consequences 12 to 14years after screening in women with FP mammograms [ 10 , 24 ]. In colorectal cancer screening programs, one Danish study reported short-term and long-term psychosocial consequences of receiving a FP or diagnosis of polyps compared to a negative screening result using a condition-specific questionnaire [ 25 ].…”
Section: Discussionmentioning
confidence: 99%